2019
DOI: 10.3390/nu11092156
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Changes in Microbiota and Liver Steatosis Induced by High-Fat Feeding—A Review of Rodent Models

Abstract: Several studies have observed that gut microbiota can play a critical role in nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) development. The gut microbiota is influenced by different environmental factors, which include diet. The aim of the present review is to summarize the information provided in the literature concerning the impact of changes in gut microbiota on the effects which dietary fat has on liver steatosis in rodent models. Most studies in which high-fat feeding h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 88 publications
3
26
0
1
Order By: Relevance
“…Most investigators posit that, under conditions of high fat, the gut microbiota of rodents increases the abundance of Firmicutes and decreases the abundance of Bacteroidetes . The increased Firmicutes/Bacteroidetes ratio in the gut appears to weaken the barrier function of the intestinal epithelium and increase LPS levels in plasma, which is conducive to the formation of endotoxemia [ 31 ]. The translocation of LPS from the intestinal epithelium to the pelvic cavity is then conducive to the maintenance of pelvic inflammation [ 13 ], which might provide a favorable environment for ectopic endometrial implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigators posit that, under conditions of high fat, the gut microbiota of rodents increases the abundance of Firmicutes and decreases the abundance of Bacteroidetes . The increased Firmicutes/Bacteroidetes ratio in the gut appears to weaken the barrier function of the intestinal epithelium and increase LPS levels in plasma, which is conducive to the formation of endotoxemia [ 31 ]. The translocation of LPS from the intestinal epithelium to the pelvic cavity is then conducive to the maintenance of pelvic inflammation [ 13 ], which might provide a favorable environment for ectopic endometrial implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[57,58] Recently, Gómez-Zorita et al have summarized present rodent studies that demonstrate the roles of altered gut microbiota in the modulation of hepatic steatosis induced by increased intake of dietary fat. [59] Therefore, combined with current investigations, we summarized the major changes in the gut microbiota of humans and animal models with liver diseases ( Table 1). However, the findings exhibit contradictory results when comparing different bacterial taxonomic composition between patients with NAFLD/NASH and control subjects.…”
Section: The Impact Of Gut Microbiota and Its Metabolites On Nafldmentioning
confidence: 99%
“…Other studies have confirmed that LAB have a variety of important physiological functions in the human body, such as maintaining micro-ecological balance, producing nutrition, and stimulating the development of tissues [10]. When probiotic bacteria are low in numbers and harmful bacteria increase, many reactions slow in the body, such as the immune response, inflammatory cells increase, thus, causing a series of metabolic disorders [11,12]. The unique physiology of LAB has allowed them to be widely used in the food, medicine, and other industries [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that LAB have an anti-oxidative effect and enhance immunity in vivo [11,12]. The present study tested the ability of Lactobacillus plantarum HFY05 (LP-HFY05) to regulate oxidative stress in alcohol-injured mice.…”
Section: Introductionmentioning
confidence: 99%